2002
DOI: 10.1128/iai.70.1.19-26.2002
|View full text |Cite
|
Sign up to set email alerts
|

Serum Stimulates Growth of and Proteinase Secretion byAspergillus fumigatus

Abstract: Serum contains iron-binding proteins, which inhibit the growth of most pathogenic microorganisms, including fungi. The purpose of this research was to investigate the effect of serum on growth of the opportunistic fungal pathogen Aspergillus fumigatus. Supplementing minimal essential medium (MEM) with up to 80% human serum or up to 80% fetal bovine serum (FBS) stimulated growth and increased the amount of A. fumigatus dry biomass approximately fourfold. In addition, a 100-fold increase in proteinase secretion,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
61
0
5

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 52 publications
2
61
0
5
Order By: Relevance
“…It seems A. fumigatus is able to use iron in serum and that a combination of available iron and protein in serum permits abundant growth of the pathogen. 21 Second, the mechanism by which A. fumigatus obtains iron in serum-containing media has recently been revealed. Five siderophores were purified from A. fumigatus culture medium, and the two major siderophores were identified as triacetylfusarinine C and ferricrocin.…”
Section: Discussionmentioning
confidence: 99%
“…It seems A. fumigatus is able to use iron in serum and that a combination of available iron and protein in serum permits abundant growth of the pathogen. 21 Second, the mechanism by which A. fumigatus obtains iron in serum-containing media has recently been revealed. Five siderophores were purified from A. fumigatus culture medium, and the two major siderophores were identified as triacetylfusarinine C and ferricrocin.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, GiVord et al [5] have shown that induction of protease secretion occurs in A. fumigatus cultured in the presence of human or fetal bovine serum (FBS) and that it may, in part, contribute to the release of iron from ironbinding proteins by proteolysis. These authors noted that iron levels were undetectable in MEM and that FBS contained 20 M iron (equivalent to 1-4 M iron in 5-20% (v/ v) FCS).…”
Section: Diverential Expression Of Ctsd Under Alternative Culture Conmentioning
confidence: 99%
“…The degradative properties of secreted proteases have attracted much attention as potential mediators of fungal invasion in infected tissue, conidophore development and iron acquisition [4,5]. For instance, the role of aspartic proteases in particular has been extensively investigated in the yeast Candida albicans and studies have shown that these key virulence factors are associated with hyphal formation, phenotypic switching, adhesion and evasion of the host immune response [6].…”
mentioning
confidence: 99%
“…A. fumigatus is one of the few pathogenic organisms that readily grows in the presence of serum (18) due to its ability to extract iron from human transferrin in this iron-limited environment (19). Furthermore, A. fumigatus can use serum proteins for biomass generation (20,21), but the full effect of serum on the cellular processes of A. fumigatus and its relevance to disease is not fully understood.…”
mentioning
confidence: 99%